Climate change policy landscape in Uganda: assessing the extent of implementation of adaptation policies at the sub-national level - Kisambira, Zepher N.; Songcai, You; Bomuhangi, Allan (Informa UK Limited, 2025)
While climate change policies in Uganda are formulated by central government bodies, implementation takes place at the local government levels, as these were identified as well-placed government institutions capable of helping rural citizens adapt to the impacts of climate change. For a systematic follow-up of why and how climate change adaptation policies in the country are working or failing, this study applies an empirical examination consisting of focus group discussions, key informant interviews, and literature reviews as a mechanism to establish the extent of implementation of a selected set of climate change adaptation policies at the sub-national level, taking Mityana district as a case study. Findings reveal that only a few climate change adaptation projects have been implemented compared to the planned projects identified in national policies and plans, mainly due to inadequate funding. Less than 1% of the district budget is directed to climate action, with the majority of these funds allocated to wages, while activities relating to disaster preparedness and management are not funded at all. There is also a general lack of awareness about climate change adaptation policies, coupled with limited technical expertise regarding the mainstreaming of climate change into development plans and budgets at the district and community levels. We propose that the national government incorporates climate change and disaster management components into all conditional grants transferred to local governments while ensuring constant monitoring, reporting, and evaluation for effective policy implementation.